2012
DOI: 10.1155/2012/106502
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Issues in Inflammatory Bowel Disease: An Overview

Abstract: Inflammatory bowel disease (IBD) including Crohn's disease (CD) and ulcerative colitis (UC) is a chronic and disabling disease with unknown etiology. There have been some controversies regarding the role of psychological factors in the course of IBD. The purpose of this paper is to review that role. First the evidence on role of stress is reviewed focusing on perceived stress and patients' beliefs about it in triggering or exacerbating the course of IBD. The possible mechanisms by which stress could be transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
140
1
14

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(186 citation statements)
references
References 90 publications
9
140
1
14
Order By: Relevance
“…Apesar da origem da DII não ser conhecida, acredita-se que fatores genéticos, imunitários e ambientais interajam juntos. Isto é, se já existe uma predisposição genética, certos fatores ambientais e psicológicos podem influenciar as defesas imunitárias e desencadear os sintomas (Sajadinejad, Asgari, Molavi, Kalantari, & Adibi, 2012a).…”
Section: Revista Iberoamericana De Diagnóstico Y Evaluación -E Avaliaunclassified
See 1 more Smart Citation
“…Apesar da origem da DII não ser conhecida, acredita-se que fatores genéticos, imunitários e ambientais interajam juntos. Isto é, se já existe uma predisposição genética, certos fatores ambientais e psicológicos podem influenciar as defesas imunitárias e desencadear os sintomas (Sajadinejad, Asgari, Molavi, Kalantari, & Adibi, 2012a).…”
Section: Revista Iberoamericana De Diagnóstico Y Evaluación -E Avaliaunclassified
“…Ainda que a alexitimia não seja específica de doentes com DII pode, no entanto, fazer com que os pacientes traduzam o sofrimento psicológico através de sintomas somáticos em vez de o fazerem pela comunicação verbal (Sajadinejad et al, 2012a). De facto, o estudo de Lunazzi de Jubany (2000) demonstra diferenças entre uma população normativa e uma psicossomática, sendo a alexitimia superior na segunda.…”
Section: Alexitimiaunclassified
“…This may occur particularly when patients have limited perceived social support or personality traits such as introversion. Regardless of whether alexithymia is specific to IBD, it has been reported that affected patients have greater difficulty in describing their feelings to others, poorer disease outcome, lower psychological functioning, and worse HRQOL [12,47,51] . Adolescents with IBD have mild cognitive problems compared to the same population with juvenile idiopathic arthritis, particularly in the acute phase.…”
Section: Psychiatric Therapy In Ibdmentioning
confidence: 99%
“…This study (Trindade, Ferreira, & Pinto-Gouveia, 2017) has namely revealed the impact of cognitive fusion and rumination on depressed mood measured one and a half year later, in a sample of patients with inflammatory bowel disease (IBD). This study seems to establish the impact of cognitive fusion on psychopathology in IBD, a condition often considered as lacking empirical support regarding the effects of associated psychological mechanisms on patients' diminished quality of life and clinical evolution (e.g., McCombie, Mulder, & Gearry, 2013;Sajadinejad, Asgari, Molavi, Kalantari, & Adibi, 2012).…”
Section: What Does This Study Add?mentioning
confidence: 99%